2019
DOI: 10.1123/ijspp.2018-0428
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Novel Trunk-Strength Assessment for High-Performance Sprint Flat-Water Kayakers

Abstract: Purpose: To determine the reliability and validity of a novel trunk maximal isometric force assessment involving 7 different tasks with 200-m times for elite sprint flat-water kayakers. Methods: Ten elite sprint flat-water kayakers performed a series of maximal isometric voluntary contractions (MVCs) on 2 separate days to assess reliability. MVC force was assessed as the participants sat on a modified kayak ergometer and applied their maximal isometric force to a uniaxial load cell during 7 different tasks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…To determine strength of kayakers, basic tests such as the overhead medicine ball throw ( López-Plaza et al, 2018 ), one-repetition maximum (1RM) tests of compound movements including bench press and prone bench pull exercises ( McGuigan et al, 2013 ; McKean and Burkett, 2010 , 2014 ; Ualí et al, 2012 ), isokinetic tests of elbow flexors ( Clarkson et al, 1982 ), shoulder extension ( Tesch, 1983 ), isometric tests including the hand grip ( Hamano et al, 2015 ), and the bilateral prone bench pull and one arm cable row ( Ualí et al, 2012 ) are used. Several attempts to develop more specific tests consisted of using simulation of the kayak stroke (i.e., to exert a pulling force in the horizontal direction involving trunk rotation, shoulder extension, and elbow flexion in one motion) with an isokinetic device ( Van Someren and Howatson, 2008 ) and tasks under isometric conditions ( Steeves et al, 2018 ). To date, the most specific dry-land test consists of recording maximal power during cycling movements performed on a modified kayak ergometer (kayak Wingate test) ( Van Someren and Howatson, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…To determine strength of kayakers, basic tests such as the overhead medicine ball throw ( López-Plaza et al, 2018 ), one-repetition maximum (1RM) tests of compound movements including bench press and prone bench pull exercises ( McGuigan et al, 2013 ; McKean and Burkett, 2010 , 2014 ; Ualí et al, 2012 ), isokinetic tests of elbow flexors ( Clarkson et al, 1982 ), shoulder extension ( Tesch, 1983 ), isometric tests including the hand grip ( Hamano et al, 2015 ), and the bilateral prone bench pull and one arm cable row ( Ualí et al, 2012 ) are used. Several attempts to develop more specific tests consisted of using simulation of the kayak stroke (i.e., to exert a pulling force in the horizontal direction involving trunk rotation, shoulder extension, and elbow flexion in one motion) with an isokinetic device ( Van Someren and Howatson, 2008 ) and tasks under isometric conditions ( Steeves et al, 2018 ). To date, the most specific dry-land test consists of recording maximal power during cycling movements performed on a modified kayak ergometer (kayak Wingate test) ( Van Someren and Howatson, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tables 1 and 2 summarise the characteristics of the included studies and the investigated measurement properties. [40,43,54,57,62,68], four had very good ROB for criterion validity [43,57,60,63], and one rated as very good ROB for construct validity [47,52]. The remaining studies were rated as either doubtful or with inadequate ROB [37, 39, 41, 42, 45, 47-53, 56, 58, 60, 61, 63, 65, 67].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eight studies assessed the intra-rater reliability of digital loading cells [36,40,41,48,49,51,54,62]. All reported sufficient intra-rater reliability for flexion, extension, and rotation against the COSMIN for good measurement properties where ICCs across all studies ranged from 0.75-1.00.…”
Section: Digital Loading Cell Asymptomatic Individualsmentioning
confidence: 99%
“…In this seminal study, they reported significant positive correlations between power output and peak shoulder and trunk flexion, trunk and pelvis rotation motion ranges, and hip, knee, and ankle flexion motion ranges. Using kayak ergometer data, others reported a high correlation between the summation of maximal voluntary contraction scores of 7 different tasks and the measured 200m performance times on the water (Steeves et al, 2019). Others reported the importance of high force output changes to high power output in long-distance kayakers (Borges, Dascombe, Bullock, & Coutts, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier reports showed the feasibility and reproducibility of various measurements during training (Fleming, Donne, Fletcher, & Mahony, 2012;Tay & Kong, 2018;, in laboratory environments and on-water (Bjerkefors et al, 2019;Steeves et al, 2019;Winchcombe, Binnie, Doyle, Hogan, & Peeling, 2019). However, sophisticated parallel data collecting, processing, and feedback systems still need to be established for kayakers.…”
Section: Introductionmentioning
confidence: 99%